Familial Association of Gilberts and Beta Thalassemia Trait (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
A 21 yrs old male from Jatrabari, Dhaka became unfit to travel to Gulf, as his serum bilirubin was found 5.7 mg/dl. He was diagnosed to have Thalassemia trait along with Gilberts syndrome. His elder brother has also got similar diseases from age 14. Here both associations of these diseases with positive family history are highlighted.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19425